Ecological study of zooplankton in the Shatt Al-Basrah canal, Basrah-Iraq - Abbas, M.F. (Mesopotamian Journal of Marine Sciences, 2022)
Seasonal abundance and distribution of Zooplankton were studied at three stations in the Shatt Al-Basrah canal, during the period from 2 April 2011 to 2 January 2012. The lowest value of zooplankton density recorded was 5 ind./m3 at station one in winter 2012, and the highest was 621200 ind./m3 at station three in spring 2011. Rotifera were dominated the zooplankton community (55%), followed by Copepoda (27%) then by Cirripede larvae (13%). Water temperatures, salinity, pH, dissolved oxygen and turbidity were measured at each station, as well as some ecological indices were calculated. Water temperature ranged from 12 to 33.2 ºC at stations one and three, respectively. Salinity values changed from 15.6 to 35.1 psu at stations one and three respectively with a decline in spring and an increase in summer. pH values were on the alkaline side, dissolved oxygen varied from 2.53 to 8.7 mg/l in spring and autumn at stations three and one, respectively. The maximum diversity index value was 0.7 at station one, richness index values was 0.54 at station three and evenness index value was 0.87 at station two. Higher similarity was obtained between stations 1 and 3 and lower value recorded between stations 2 and 3.